Pathophysiology of CD4+ T-Cell Depletion in HIV-1 and HIV-2 Infections - Vidya Vijayan, K. K.; Karthigeyan, Krithika Priyadarshini; Tripathi, Srikanth P.; Hanna, Luke Elizabeth (Frontiers in Immunology, 2017)
The hall mark of human immunodeficiency virus (HIV) infection is a gradual loss of CD4+ T-cells and imbalance in CD4+ T-cell homeostasis, with progressive impairment of immunity that leads ultimately to death. HIV infection in humans is caused by two related yet distinct viruses: HIV-1 and HIV-2. HIV-2 is typically less virulent than HIV-1 and permits the host to mount a more effective and sustained T-cell immunity. Although both infections manifest the same clinical spectrum, the much lower rate of CD4+ T-cell decline and slower progression of disease in HIV-2 infected individuals have grabbed the attention of several researchers. Here, we review the most recent findings on the differential rate of decline of CD4+ T-cell in HIV-1 and HIV-2 infections and provide plausible reasons for the observed differences between the two groups.